Unfortunately, limitations of the browser used by Answers.com means that we cannot see most symbols. It is therefore impossible to give a proper answer to your question. Please resubmit your question spelling out the symbols as "plus", "minus", "times", "divided by", "equals".
Your two equations are: AX + BY = A - B BX - AY = A + B + B Because you have four variables (A, B, X, Y), you cannot solve for numerical values for X and Y. There are a total of four answers to this question, solving each equation for X and Y independently. First equation: X = (A - B - BY)/A Y= (A - B - AX)/B Second equation: X = (A +2B +AY)/B Y = (BX - A - 2B)/A
You cannot solve an expression. You need an equation or inequality.You cannot solve an expression. You need an equation or inequality.You cannot solve an expression. You need an equation or inequality.You cannot solve an expression. You need an equation or inequality.
ax + by + cz + d = 0At the z-intercept, 'x' and 'y' are both zero.cz + d = 0 --> z = -d/c --> The z-intercept is the point (0, 0, -d/c).At the x-intercept, 'y' and 'z' are zero.ax + d = 0 --> x = -d/a --> The x-intercept is the point (-d/a, 0, 0).The distance between the points (0, 0, -d/c) and (-d/a, 0, 0) issqrt[ (-d/a)2 + (-d/c)2 ] = sqrt (d2/a2 + d2/c2) = d sqrt(1/a2 + 1/c2)
plug the x coordinate in the x part of the equation and plug the y coordinate in the y's part of the equation and solve
let f(x) = ax if a is a constant, then f'(x) = a if a is not constant, then f'(x) = ax' + a'x
ax - b = c ax = b + c x = (b + c)/a
x = (d-a)/(a-c)
For example, the equation of a line: y = ax + b. the equation of a curve: y = cx2 + dx + e ax + b = cx2 + dx + e (solve for x)
For an equation of the form ax² + bx + c = 0 you can find the values of x that will satisfy the equation using the quadratic equation: x = [-b ± √(b² - 4ac)]/2a
Your two equations are: AX + BY = A - B BX - AY = A + B + B Because you have four variables (A, B, X, Y), you cannot solve for numerical values for X and Y. There are a total of four answers to this question, solving each equation for X and Y independently. First equation: X = (A - B - BY)/A Y= (A - B - AX)/B Second equation: X = (A +2B +AY)/B Y = (BX - A - 2B)/A
The answer depends on what form the equation is in and what form you want it in. The standard form is ax + by +c = 0 where x and y are variables and a, b and c are constants. There are also the 1-d equivalent: ax + b = 0 and 3-d equivalent: ax + by + cz + d = 0 and, equivalent equations in spaces with higher dimensions.
plug in a 0 for the "x" value of the equation, and solve it :D
Before this question can be answered, you'll need to rewrite the equation in a legible manner. Do you mean: ax + by = czd? ax - by + cz = d? ax + by + czd? (not even an equation) Please use spoken words to express your question when the form won't accept symbols. For example, the first of those equations could be expressed as "a times x plus b times y equals c times z to the power of d".
First rearrange the linear equation to the form ax + b = cThen subtract b from both sides: ax = c - b Divide both sides by a: x = (c - b)/a
The expression you presented is not an equation. Do you mean ax2 + bx = c? Do you mean to solve it for x? I'm assuming that's the case, but you need to be more clear on your question. To solve for x then, the technique to use is called completing the square: ax2 + bx = c Multiply both sides by a: a2x2 + abx = ac Add the square of b/2 to both sides: a2x2 + abx + (b/2)2 = ac + (b/2)2 We now have a perfect square on the left, simplify: (ax + b/2)2 = ac + b2 / 4 (ax + b/2)2 = (4ac + b2) / 4 And now solve for x: ax + b/2 = ±[(4ac + b2) / 4]1/2 ax + b/2 = ± √(4ac + b2) / 2 ax = [-b ± √(4ac + b2)] / 2 x = [-b ± √(4ac + b2)] / 2a
To solve an equation for x, you need to isolate the variable on one side of the equation. Start by performing the inverse operation to undo any addition, subtraction, multiplication, or division. Once you have x by itself, the solution will be the value of x that satisfies the equation. Remember to follow the order of operations and be careful with signs to ensure accuracy in your answer.
-- At the z-intercept, x=0, y=0, cz=d, so z=d/c.-- At the x-intercept, y=0, z=0, ax=d, so x=d/a.The distance between the two points is sqrt[ (d/c)2 + (d/a)2 ] or d sqrt[ (1/c)2 + (1/a)2 ].